2016
DOI: 10.1080/19440049.2016.1269207
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of dietary exposure to tryptamine for the Austrian population

Abstract: Tryptamine acts as a neuromodulator and vasoactive agent in the human body. Dose-response data on dietary tryptamine are scarce and neither a toxicological threshold value nor tolerable levels in foods have been established so far. This paper reviews dose-response characteristics and toxicological effects of tryptamine as well as tryptamine contents in food, estimates dietary exposure of Austrian consumers, and calculates risk-based maximum tolerable limits for food categories. A dose without effect of 8 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…Beginning on day 1, mice received a 50 µL intraperitoneal injection containing either a vehicle (sterile corn oil (CO) with 2% DMSO v/v) or a treatment suspension (12.5 mg/kg tryptamine in sterile CO with 2% DMSO v/v) every 48 h. This dose of 12.5 mg/kg was chosen in accordance with previous studies that have demonstrated it to be a safe dose that will not induce short term behavioral changes in mice (Mousseau, 1993). This dose was also deemed to be safe and clinically relevant when converted to a human equivalent dose of 1 mg/kg (Nair and Jacob, 2016;Wüst et al, 2017).…”
Section: Induction Of Chronic Progressive Eae and Treatment With Tryptaminementioning
confidence: 99%
“…Beginning on day 1, mice received a 50 µL intraperitoneal injection containing either a vehicle (sterile corn oil (CO) with 2% DMSO v/v) or a treatment suspension (12.5 mg/kg tryptamine in sterile CO with 2% DMSO v/v) every 48 h. This dose of 12.5 mg/kg was chosen in accordance with previous studies that have demonstrated it to be a safe dose that will not induce short term behavioral changes in mice (Mousseau, 1993). This dose was also deemed to be safe and clinically relevant when converted to a human equivalent dose of 1 mg/kg (Nair and Jacob, 2016;Wüst et al, 2017).…”
Section: Induction Of Chronic Progressive Eae and Treatment With Tryptaminementioning
confidence: 99%
“…For the Austrian population, the maximum intake of BAs in fermented meat products was evaluated: adult female/male putrescine (PUT) 1.1/1.9 mg/day and cadaverine (CAD) 1.8/3 mg/day [ 12 ]. The TRPs for women and men were 23.4, 42.0, and 71.7 mg/day [ 13 ]. Therefore, restraining the content of various biogenic amines in fermented meat products has become the focus of consumers, especially patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, the risk assessment of dietary exposure to tryptamine was analyzed for the Austrian population [ 24 ]. For fresh/cooked fish, preserved fish, cheese, raw sausage, condiments, sauerkraut and fermented tofu, maximum tolerable levels of tryptamine were 1650; 3200; 2840; 4800, 14120; 1740; and 2400 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this report, we revisited our data to analyze them together with other related publications to shed light on different aspects of AD modelling. This approach prompts us to suggest the model-based disease concept that (1) the tryptophan metabolite tryptamine present in different dietary products in different geographical locations [ 21 , 22 , 23 , 24 , 25 ], produced by human gut microbes [ 10 ], inhibit the host protein biosynthesis via the TrpRS deficiency that leads to neurodegeneration and cell death in human organs [ 4 ]; (2) the microbial production of tryptamine can be modified by human diet and dietary supplements that can cause significant increase (six-fold) in excreted tryptamine [ 26 ]; (3) prescription drugs—antidepressants ( inhibitors of monoamine oxidase (MAO catabolizing tryptamine to indole-3-acetic acid (IAA)) potentiate the tryptamine activities causing seizures and death in animals [ 27 ]; (4) usage of antibiotics increases the tryptamine production in animals [ 9 , 28 ]; and (5) the levels of tryptamine (~10 mg/kg) is higher than those of tryptophan (~1 mg/kg) in transgenic potato tubers expressing tryptophan decarboxylase [ 29 ]. TrpRS activities can also be altered in vivo because (i) TrpRS is the interferon-inducible protein [ 30 ]; (ii) TrpRS is a secreted dietary protein that can be consumed with a cow milk [ 31 , 32 , 33 ]; (iii) TrpRS is a human autoantigen and anti-TrpRS autoantibodies bind both human and bovine TrpRS [ 34 ]; (iv) TrpRS expression is modulated by hypoxia [ 35 ].…”
Section: Introductionmentioning
confidence: 99%